2003
DOI: 10.1152/jn.01014.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Expectations for Different Reward Magnitudes on Neuronal Activity in Primate Striatum

Abstract: In behavioral science, it is well known that humans and nonhuman animals are highly sensitive to differences in reward magnitude when choosing an outcome from a set of alternatives. We know that a realm of behavioral reactions is altered when animals begin to expect different levels of reward outcome. Our present aim was to investigate how the expectation for different magnitudes of reward influences behavior-related neurophysiology in the anterior striatum. In a spatial delayed response task, different instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
254
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(287 citation statements)
references
References 89 publications
28
254
3
2
Order By: Relevance
“…encoding of stimulus-reward associations (18,19) and cue-induced reward expectation (20,21). Human functional neuroimaging data also demonstrate ventral striatal activity to cue presentation following appetitive and aversive Pavlovian conditioning (22).…”
Section: Discussionmentioning
confidence: 96%
“…encoding of stimulus-reward associations (18,19) and cue-induced reward expectation (20,21). Human functional neuroimaging data also demonstrate ventral striatal activity to cue presentation following appetitive and aversive Pavlovian conditioning (22).…”
Section: Discussionmentioning
confidence: 96%
“…Afferent projections to the VS, like those to the dorsal striatum are derived from three major sources: a massive, generally topographic glutamatergic input from cerebral cortex; a large glutamatergic input from the thalamus; and a smaller, but critical input from the brainstem, primarily from the midbrain dopaminergic cells. Although this section primarily focuses on the connections of the VS, it gives some attention to the dorsal striatum, especially the caudate nucleus, an area that is also involved in reward-based learning (Cromwell and Schultz, 2003;Kennerley and Wallis, 2009;Watanabe and Hikosaka, 2005). This region receives input from the dPFC.…”
Section: Organization Of the Vsmentioning
confidence: 99%
“…Other studies of electrophysiology and dopamine release in rats have also shown that both neuronal firing or dopamine release tend to signal the "better" of two reward options rather than their absolute value (Day et al, 2010;Roesch et al, 2007). Studies in monkeys have also tried to address whether striatal activations incorporate details of upcoming rewards and have demonstrated differences in activation patterns induced by two different types of juices (Hassani et al, 2001) as well as rewards of different magnitudes (Cromwell and Schultz, 2003). Finally, human neuroimaging studies have shown a specific relationship between BOLD signal increase in the NAc and magnitude of reward (Cooper and Knutson, 2008;Knutson and Cooper, 2005;Yacubian et al, 2006) and dichotomous activation for the cue predicting the greatest available reward value has also been observed (Ballard and Knutson, 2009).…”
Section: Nucleus Accumbens Activation and Reward Magnitude Codingmentioning
confidence: 99%